PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP PREFERENSI KONSUMEN AYAM POTONG (STUDI KASUS AYAM POTONG MAS ADI DI DESA DU SKPA) - Desviana Safitri; Hendry Kurniawan; Heffi Christya Rahayu (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the influence of product quality and price on consumer preferences for Mas Adi's broiler chicken in DU SKPA Village. Empirical phenomena in the field indicate that there are differences in consumer preferences in choosing where to buy broiler chicken in DU SKPA Village. Consumers tend to prefer buying broiler chicken from Mas Adi's business compared to other sellers because they consider the quality of the product and the price offered. This study uses a quantitative approach with a multiple linear regression analysis method processed using SPSS version 21 software. The study population includes all consumers of Mas Adi's broiler chicken in DU SKPA Village, whose number is unknown. The sampling technique used was accidental sampling, with the number of samples determined based on the formula of Hair et al., resulting in 140 respondents. Data collection was carried out through observation, interviews, and distributing questionnaires to consumers of Mas Adi's broiler chicken who served as research respondents. The collected data were then analyzed to identify the influence of each independent variable on the dependent variable. The results of the analysis indicate that product quality has a positive and significant effect on consumer preferences for Mas Adi's broiler chicken in DU SKPA Village. In addition, price has also been shown to have a positive and significant effect on consumer preferences. Simultaneously, the product quality and price variables have a positive and significant effect on consumer preferences for Mas Adi's broiler chicken in DU SKPA Village.